Characterization, mutagenesis and mechanistic analysis of an ancient algal sterol C24-methyltransferase: Implications for understanding sterol evolution in the green lineage. (May 2015) - Haubrich, Brad A.; Collins, Emily K.; Howard, Alicia L.; Wang, Qian; Snell, William J.; Miller, Matthew B.; Thomas, Crista D.; Pleasant, Stephanie K.; Nes, W. David
Graphical abstract: Cloned sterol C24-methyltransferase from Chlamydmonas reinhardtii generates multiple products and possesses broad substrate specificity. The C24-methylation pathway proceeds through the Δ 25(27) -olefin route which furnishes the 24β-methyl group in algal ergosterol. Highlights: C. reinhardtii sterol C24-methyltransferase (SMT) is bi-functional for substrate. Cr SMT efficiently recognizes unnatural substrates from fungi and land plants. 2 H/ 13 C-Isotopic labeling studies show Cr SMT catalysis operates via the Δ 25(27) -route. Site-directed mutagenesis of Tyr110 results in metabolic switching in C24-methylation. Mutational divergence of a promiscuous SMT may be the basis for sterol diversity. Abstract: Sterol C24-methyltransferases (SMTs) constitute a group of sequence-related proteins that catalyze the pattern of sterol diversity across eukaryotic kingdoms. The only gene for sterol alkylation in green algae was identified and the corresponding catalyst from Chlamydomonas reinhardtii (Cr) was characterized kinetically and for product distributions. The properties of Cr SMT were similar to those predicted for an ancient SMT expected to possess broad C3-anchoring requirements for substrate binding and formation of 24β-methyl/ethyl Δ 25(27) -olefin products typical of primitive organisms. Unnatural Δ 24(25) -sterol substrates, missing a C4β-angular methyl group involved with binding orientation, convert to product ratios in favor of Δ 24(28) -products. Remodeling the active site to alter the electronics of Try110 (to Leu) results in delayed timing of the hydride migration from methyl attack of the Δ 24 -bond, that thereby produces metabolic switching of product ratios in favor of Δ 25(27) -olefins or impairs the second C1 -transfer activity. Incubation of [27- 13 C]lanosterol or [ methyl - 2 H3 ]SAM as co-substrates established the Cr SMT catalyzes a sterol methylation pathway by the "algal" Δ 25(27) -olefin route, where methylation proceeds by a conserved S N 2 reaction and de-protonation proceeds from the pro- Z methyl group on lanosterol corresponding to C27. This previously unrecognized catalytic competence for an enzyme of sterol biosynthesis, together with phylogenomic analyses, suggest that mutational divergence of a promiscuous SMT produced substrate- and phyla-specific SMT1 (catalyzes first biomethylation) and SMT2 (catalyzes second biomethylation) isoforms in red and green algae, respectively, and in the case of SMT2 selection afforded modification in reaction channeling necessary for the switch in ergosterol (24β-methyl) biosynthesis to stigmasterol (24α-ethyl) biosynthesis during the course of land plant evolution.